Solistiyhtye Oiva Lampinen Ami & Olli - Heinonen, Olavi; Lampinen, Oiva; Palonen, Jari; Souru, Jorma; Varjotie, Ami (Solistiyhtye Oiva Lampinen Ami & Olli, 1995)
15 kappaletta.
Keywords: Lampinen, Oiva : albumit; Varjotie, Ami : albumit